Pareto-Improving Social Security Reform when Financial Markets Are Incomplete!? - Krueger, Dirk; Kubler, Felix (American Economic Review, 2006)
This paper studies an overlapping generations model with stochastic production and incomplete markets to assess whether the introduction of an unfunded social security system leads to a Pareto improvement. When returns to capital and wages are imperfectly correlated, a system that endows retired households with claims to labor income enhances the sharing of aggregate risk between generations. Our quantitative analysis shows that, abstracting from the capital crowding-out effect, the introduction of social security represents a Pareto-improving reform, even when the economy is dynamically efficient. However, the severity of the crowding-out effect in general equilibrium tends to overturn these gains.